Engaging in continuous improvement: implications for educator preparation programs and their mentors - Brondyk, Susan K. (Frontiers in Education, 2024)
This is a mixed method study that examines how one Educator Preparation Program designed and used an assessment tool to promote growth in their teacher candidates. The tool became central to the identity of the program and foundational to the work of the mentors. Data includes the statistical analysis of seven semesters of assessment data, along with qualitative interviews, recordings of mentor training sessions, three-way mentor conversations, and written materials.Research questions include: How do tools contribute to the identity of a program question? What value does using an internally-designed evaluation tool add to an educator preparation program?The findings indicate that the practice of the mentors became more developmentally-oriented over time. This suggests that engaging in the process of creating, adapting, and using an internally-designed instruments contributes to a shared identity that reflects the values of the program and provides direction to all.